IMPLEMENTASI PENGEMBANGAN MODEL ENTREPRENEURSHIP BERBASIS KAPABILITAS INSANI MAHASISWA - Bagis, Abdul Azis; Surati, Surati; Kusumayadi, Iwan (Master of Management, Mataram University, 2019)
Today's Indonesian university graduates are facing the challenges of the business world and the increasingly turbulent (chaotic) world of work, with a variety of fundamental changes, not easily predictable, because they do not have a clear pattern and take place continuously. Science and entrepreneurship skills obtained from college, can experience obsolescence, in the midst of increasingly rapid demands for progress. Facing such a situation, what is needed is not only the ability to adapt for a moment, but also the willingness and determination to always adapt to developments that occur on an ongoing basis. Policy. The method of teaching entrepreneurship needs to be integrated (synergize), the content of knowledge and skills (transfer of business knowledge and skills), which comes from outside-in (outside-in), with the process of actualizing the inner-out entrepreneurship, so that expressing their entrepreneurial ideals and spirit, becoming human capability of Indonesian students.Keywords : inside-out, outside-in, human potential, competence, virtues The implementation of the development of an entrepreneurship model that relies on the capabilities of human students, proves that college graduates, are able to become entrepreneurs to their expectations. With the support of a conducive academic climate, which is based on virtues, and the concerns of the parties concerned, while strengthening the implementation of entrepreneurship model development, in giving birth to scholars of entrepreneurs becoming superior, independent and competitive human beings in the global environment. It is hoped that the results of the study will be aimed at implementing and developing effective models of entrepreneurship, for the birth of young entrepreneurs from universities, especially students at the University of Mataram.